Chylomicronemia Mimicking an Infection During Emergent Fracture Surgery: A Case Report. Issue 2 (April 2021) - Pieringer, Alexander; Sprengel, Kai; Pape, Hans-Christoph; Neuhaus, Valentin
Abstract : Case: A 36-year-old patient with chronic alcohol abuse and previous medical history of total hip arthroplasty suffered a fracture of the femoral shaft. During osteosynthesis, a milky fluid similar to purulent discharge emerged at multiple locations. Immediate Gram stains were negative, and the surgery was performed as planned. Laboratory tests showed massive elevated levels of triglycerides. During further workup, chylomicronemia syndrome was diagnosed. Conclusion: This case report shows that chylomicronemia syndrome can have an appearance during surgery similar to a purulent infection. Immediate Gram stains and laboratory work can identify the reason.